Pengaruh Elemen Fraud Diamond Theory Terhadap Financial Statement Fraud - Ranti Tri Annisa; Halmawati Halmawati (Jurnal Eksplorasi Akuntansi, 2020)
The purpose of this study was to determinate the effect fraud diamond theory in financial statement fraud. The population in this study are manufacturing companies sector consumer goods industry listed on the Indonesia Stock Exchange in 2015-2018. The sampling technique used was purposive sampling method and obtained 112 samples. Data analysis using multiple linear regression analysis techniques and processed with IBM SPSS Statistics 25 software. The results showed that the financial target, ineffective monitoring, auditor report and changes in directors had a simultaneous effect on financial statement fraud. Partially, financial target affect financial statement fraud, while ineffective monitoring, auditor report and change of director do not affect the financial statement fraud.